Invasive prey controlling invasive predators? European rabbit abundance does not determine red fox population dynamics. Issue 6 (24th August 2018) - Scroggie, Michael P.; Forsyth, David M.; McPhee, Steven R.; Matthews, John; Stuart, Ivor G.; Stamation, Kasey A.; Lindeman, Michael; Ramsey, David S. L.
Abstract: Invasive mammalian predators commonly coexist with invasive mammalian herbivore prey. Managers often advocate controlling invasive prey in the belief that this will also reduce invasive predator abundance. Such an outcome would have desirable ecological and financial benefits, but there have been few tests of this hypothesis. We used large‐scale and long‐term monitoring data to test the prediction that invasive red fox Vulpes vulpes populations decline following control of invasive European rabbit Oryctolagus cuniculus populations in Australia. Both species severely impact natural and agricultural ecosystems, and significant resources are expended to reduce these impacts. We fitted a hierarchical state‐space model to spotlight counts of both species conducted at 21 transects between 1998 and 2015. The effects of rainfall, control activities (warren ripping and surface harbour removal), and density dependence on the population growth rates of both species were also evaluated. Control activities at 18 transects substantially reduced average rabbit abundances. Rabbit populations showed little response to rainfall, but exhibited negative density dependence and higher rates of increase during the autumn–spring interval. There was no numerical response of foxes to changes in rabbit abundance. Rather, fox populations increased rapidly after high rainfall and exhibited negative density dependence. The equilibrium abundance of foxes varied with rainfall and season, but was always <0.2 foxes per spotlight km. Synthesis and applications . We conclude that controlling rabbits to low abundances does not substantially reduce fox abundances in south eastern Australia. Rather, efforts to reduce fox abundance should directly target fox populations. Managers of invasive predator–invasive prey systems should not assume that controlling prey will, by itself, reduce predator abundances. Quantifying the numerical response is critical for understanding the likely response of predators to changes in prey abundance. Abstract : We conclude that controlling rabbits to low abundances does not substantially reduce fox abundances in south eastern Australia. Rather, efforts to reduce fox abundance should directly target fox populations. Managers of invasive predator–invasive prey systems should not assume that controlling prey will, by itself, reduce predator abundances. Quantifying the numerical response is critical for understanding the likely response of predators to changes in prey abundance.